Prevalence of X-aneuploidies, X-structural abnormalities and 46, XY sex reversal in Turkish women with primary amenorrhea or premature ovarian insufficiency - SÖYLEMEZ, MEHMET ALİ (ELSEVIER SCIENCE BV, 2014)
Our objective was to identify the distribution of cytogenetic abnormalities of 175 Turkish women with primary amenorrhea (PA) or premature ovarian insufficiency (POI). A retrospective study was performed using medical records of 94 patients with PA and 81 patients with POI at the Genetics Department, Zeynep Kamil Women's and Children's Research and Training Hospital, Istanbul, Turkey. G-banded metaphase kaiyotype analysis were prepared and analyzed. Chromosomal abnormalities were present in 44 of 175 cases (25%). 15 were full blown or mosaic numerical X chromosome abnormalities (8.5%), 10 were full blown or mosaic X-chromosome structural anomalies (5.7%), one was X-autosome translocation (0.5%), 3 were autosomal anomalies (1.7%), 12 were XY kaiyotype (6.8%), one was 45,X/46,XY mosaic and 2 were full blown or mosaic structural anomalies of Y chromosome (1.7%). The prevalence of chromosomal abnormalities was 25% in this large series of Turkish women with primary amenorrhea or premature ovarian insufficiency, most cases involving X-aneuploidy or X-structural abnormalities or 46,XY karyotype. High prevalence of chromosomal abnormalities is associated with POI starting at an early age (average age: 26 years). (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Primary amenorrhea; Primary ovarian insufficiency; X-chromosome abnormalities; TURNER SYNDROME; FAILURE; MOSAICISM; GENE; VARIANTS; BMP15